2018
DOI: 10.1080/08854726.2018.1490059
|View full text |Cite
|
Sign up to set email alerts
|

Patient Reported Outcomes of Pastoral Care in a Hospital Setting

Abstract: This study aimed to establish whether Pastoral Care (PC) visits were an effective component of a hospitalised patient's overall health experience. Outcomes of PC visits were reported by 369 patients in 7 sites across Australia. The patient reported outcomes of PC visits included: the patients felt they could be honest with themselves, with a sense of peace, a better perspective of their illness, less anxiety and felt more in control. Five factors of the PC visit significantly related to higher patient's overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…Of the 503 invited to participate across the 35 sites operated by three of the organisations, 468 (93%) participated. This consent rate is substantially higher than the consent rate in other studies (Ashton et al, ; Lobb et al, ). This difference is likely due to differences in the data collection methods used; the long‐term stay of participants in RAC homes allowed for the completed questionnaires to be directly returned by, or collected from, the participants rather than posted back.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 503 invited to participate across the 35 sites operated by three of the organisations, 468 (93%) participated. This consent rate is substantially higher than the consent rate in other studies (Ashton et al, ; Lobb et al, ). This difference is likely due to differences in the data collection methods used; the long‐term stay of participants in RAC homes allowed for the completed questionnaires to be directly returned by, or collected from, the participants rather than posted back.…”
Section: Resultsmentioning
confidence: 99%
“…(Bay et al, ). Studies examining the impact of PC have predominantly been conducted in hospital settings (Ashton, Madden, & Monterosso, ; Bay et al, ; Lobb, Schmidt, Jerzmanowska, Swing, & Thristiawati, ). For example, a survey with 44 patients and bereaved carers in a large tertiary private hospital in Australia found that participants were satisfied with the PC received, finding it helpful and offered with courtesy and respect.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…To date, evaluation of this workforce in Australia has been limited. [10,11] Confusion is further exacerbated because the roles and scope of practice for different providers are not adequately defined. [12] These variations pose a risk to the quality of spiritual care and the safety of those receiving this care.…”
Section: Introductionmentioning
confidence: 99%